Charge transport properties of an organic solar cell - Yakuphanoğlu, Fahrettin; Anand, R. S. (Elsevier Science Sa, 2010)
The electronic properties of ITO/PEDOT-PSS/P3HT-PCBM/LiF/AI organic solar cell have been investigated using current-voltage and capacitance-voltage techniques. The electrical parameters like ideality factor n, series resistance R-s and barrier height phi(b), have been extracted using current-voltage and capacitance-voltage techniques. The photovoltaic parameters such as open circuit voltage V-oc short circuit current I-sc and fill factor FF were determined from current-voltage characteristics of the solar cell under illumination. The ideal value than unity for the organic solar cell indicates the presence of non-ideal behaviour. The barrier height of the solar cell is found to be dependent both temperature and applied voltage and the model of Gaussian distribution of the barrier height was presented for explaining their anomalous behaviour. The standard deviation of the barrier height distribution sigma(o) indicates the presence of interface inhomogeneities. The ideality factor n, open circuit voltage V-oc, short circuit current density J(sc), fill factor FF and Richardson constant A* values for the organic solar cell were found to be 2.29, 0.58 V.5.84 mA/cm(2), 0.31 and 10.41 A/cm(2) K-2, respectively. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Organic solar cell; metal-semiconductor device